APSIM Next Generation: Overcoming challenges in modernising a farming systems model. (May 2018) - Holzworth, Dean; Huth, N.I.; Fainges, J.; Brown, H.; Zurcher, E.; Cichota, R.; Verrall, S.; Herrmann, N.I.; Zheng, B.; Snow, V.
Abstract: From 1990, the Agricultural Production Systems sIMulator (APSIM) has grown from a field-focused farming systems framework used by a small number of people, into a large collection of models used by thousands of modellers internationally. The software grew to consist of several hundred thousand lines of code in multiple programming languages. This has led to a large, complex software ecosystem that is difficult to maintain. In addition, systems modellers increasingly require software systems that integrate multiple disciplines, can represent evermore complex farming systems, can run on multiple operating systems (desktop, web, mobile), can operate at or be adjusted to multiple temporal and spatial scales (field, farm, region, continent, global) and run faster for larger simulation analyses. This is difficult to achieve in an aging framework. For these reasons, the APSIM Initiative is building the next generation of APSIM. This manuscript outlines the approach taken and lessons learnt. Highlights: APSIM is an agricultural modelling framework used extensively worldwide. APSIM Next Generation is a new, modern rewrite of APSIM. Many lessons have been learnt during this rewrite. A good software process is important in all model development activities.